ORNAMENTED INHERITANCES IN UZBEKISTAN AND EXPLANATION TO SOME OF THEIR PARTS: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In this article it has been given information about the historical inheritances of Uzbekistan as well as their parts.it is true that learning this view is not easy, but searching and knowing these historical words meaning is necessary for everyone.